His accidental countess - Burrows, Annie (Harlequin historicals., 2021)
"From abducted... ...to betrothed! To stop an unsuitable elopement, Tobias Spenlow bundles his ward's intended bride into his carriage--only to discover he's made a terrible mistake. The woman is actually innocent governess Miss Dorothy Phillips--whose reputation he's unintentionally ruined! The only way to right this wrong is for the earl to wed her. She might have accidentally become his countess, but their consuming attraction has him courting her in earnest!"--Provided by publisher.